AKIBAT HUKUM TERHADAP PERKAWINAN BEDA AGAMA DI INDONESIA: STUDI TERHADAP PUTUSAN PN SURABAYA NOMOR 916/PDT.P/2022/PN SBY - Dimiyati, Patricia Karlina; Latumahina, Rosalinda Elsina (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The current Marriage Law in Indonesia does not specifically explain marriages with different religious backgrounds. The absence of this regulation in Indonesia has triggered various interpretations related to the licensing of interfaith marriages. Article 2 Paragraph (1) of the Marriage Law explains that a marriage has a valid status if, "A marriage carried out according to religion and belief". The verse explains that the licensing of interfaith marriages adheres to the provisions of each religion. However, other regulations such as the Marriage Law and the Regulation of the Domestic Government of the Republic of Indonesia No. 108 of 2009 Article 50 Paragraph (3) state that there is a possibility that interfaith marriages can be carried out if they have been allowed by the court. Based on this, a study was conducted to clarify the legal consequences of registering interfaith marriages with the existence of Decision No. 916/Pdt.P/2022/PN. Sby. This research is a type of normative law research or normative juridical, with a statutory and conceptual approach. Based on research that has been carried out, the existence of the Population Administration Law and Domestic Government Regulation of the Republic of Indonesia No. 108 of 2009 makes the law of interfaith marriage clearly visible and so that it becomes legally valid and can be ratified through a District Court Determination and recorded at the authorized Population and Civil Registration Office. Then, this provision is also contained in the 1945 Constitution Article 28 B Paragraph (1)